Analysis of Biochemical Indicators in Female Infertility - Mundada, Atulkumar (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Infertility affects a significant proportion of women worldwide, with various underlying causes. The biochemical assessment of hormonal and metabolic indicators can provide critical insights into the etiologies of female infertility. Biochemical indicators play a crucial role in diagnosing and understanding female infertility. Hormonal profiles, metabolic conditions, and specific biomarkers like AMH provide valuable information about ovarian function, reproductive health, and underlying pathologies. Integrating these markers into a comprehensive diagnostic approach can improve the accuracy of infertility assessments and guide personalized treatment strategies. Future research should focus on longitudinal studies to validate these biomarkers and explore their potential in therapeutic interventions. This study aims to systematically analyze the role of specific biochemical markers in diagnosing and understanding female infertility.Aim: The primary aim of this study is to evaluate the relationship between various biochemical indicators and female infertility, focusing on hormones, metabolic profiles, and other relevant biomarkers. Additionally, the study seeks to identify potential biomarkers that could enhance diagnostic accuracy and therapeutic strategies.Material and Method: A case-control study design was employed for this investigation conducted in the Department of Obstetrics and Gynecology. The study included 80 patients diagnosed with various conditions—20 with PCOS, 15 with BOH, 20 with endometriosis, and 25 with ovarian insufficiency. These patients were compared with 80 matched healthy controls. A specially designed proforma was used to gather information on personal, medical, and reproductive histories. Hormone levels for follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), progesterone (P), and testosterone (T) were measured in the participants.Results: The data suggests that women with PCOS, endometriosis, and OI experience higher oxidative stress, as indicated by elevated LPO levels. The increased SOD activity in these groups reflects a compensatory response to this oxidative stress, except in the case of OI, where SOD activity is not significantly elevated. Increased protein levels in the study groups (PCOS, endometriosis, and OI) compared to controls might indicate an inflammatory or stress-related response in these conditions. The FSH levels elevated in BOH, indicating reduced ovarian reserve. Other groups show relatively normal levels. LH Varies widely among conditions, with the lowest levels in endometriosis, possibly suggesting hypogonadism or other issues. E2 Lower in PCOS and endometriosis compared to controls, with OI showing the highest levels. T Elevated in PCOS and endometriosis, indicating possible hyperandrogenism. P Significantly lower in endometriosis and PCOS, with potential implications for reproductive health.Conclusion: The analysis of biochemical indicators in female infertility reveals significant disruptions in oxidative stress and hormonal regulation across various infertility conditions. Elevated oxidative stress, along with hormonal imbalances in FSH, LH, E2, T, and P, highlights the complexity of infertility and its underlying mechanisms. These insights are crucial for developing targeted diagnostic